(3HOGjI GdgOGjIs - (3GdYGedj, GdMQ, eMeO Hf GdMSf Hf Ydj, (B1104 (3g`s ((3eMeO gGOj Hf edG MSf NGf GdRfLGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bO GdJeS efj LeGYI ef GdENhGf GdeDefjf GdWGdHjf ddMb Gdjbjf Cf GLeY dge eG CbOQ Ydi LeYg ef efUhU GdhGLHGJ hGdeMQeGJ hdG CONd eYgeG EdG GdjSjQ ef GdeSJMHGJ (B...s
(3BNQgG (B:s
... (3Ydi GdGNJUGQ eGde jLeYg cKjQ ef GdcJH GdcHGQ hef CQGO GdGWdGY Ydi GOdJgG adjQLY Edi cJGHfG GdePchQ aj ChdgG aUGQJ GdhGLHGJ CdaG hNeSeGFI hKdGKjf hGdeMQeGJ CdaG hCQHYeGFI hKeGfjf (B...(3bO aQZJs
(3HYOgG HebOGQ KeGf hQbGJ efXheI HGdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\90s
(3gOjI GdYGQajf (B2\304s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis